L’électrification rurale décentralisée dans le sud - Nadia Bentaleb (VertigO)
In the south countries, the decentralised energy is often used in the rural electrification. In this article, we present the different renewable energy and the technological transfert condition. Finally, we present some practice of actors: the state, the NGO, the PNUD and the entreprise.